2021
DOI: 10.1002/adfm.202102874
|View full text |Cite
|
Sign up to set email alerts
|

Reassembly of MXene Hydrogels into Flexible Films towards Compact and Ultrafast Supercapacitors

Abstract: The freestanding MXene films are promising for compact energy storage ascribing to their high pseudocapacitance and density, yet the sluggish ion transport caused by the most densely packed structure severely hinders their rate capability. Here, a reassembly strategy for constructing freestanding and flexible MXene-based film electrodes with a tunable porous structure is proposed, where the Ti 3 C 2 T x microgels disassembled from 3D structured hydrogel are reassembled together with individual Ti 3 C 2 T x nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 44 publications
(75 reference statements)
1
36
0
Order By: Relevance
“…In regard to electrochemical energy storage, MXenebased materials still suffer from the intrinsic restacking tendency, reduced accessibility of electrochemical surface area, and limited ion transport. [16,17] MXene-based hybrid materials can be further developed to obtain an architecture that can empower access to nanospaces and promote ion transfer. [18][19][20][21] Thus, it is highly desired to engineer the interlayer spacing of MXenes to improve their electrolyte-accessible surface area and enhance the charge-transport properties to achieve their full chargestorage capability.…”
mentioning
confidence: 99%
“…In regard to electrochemical energy storage, MXenebased materials still suffer from the intrinsic restacking tendency, reduced accessibility of electrochemical surface area, and limited ion transport. [16,17] MXene-based hybrid materials can be further developed to obtain an architecture that can empower access to nanospaces and promote ion transfer. [18][19][20][21] Thus, it is highly desired to engineer the interlayer spacing of MXenes to improve their electrolyte-accessible surface area and enhance the charge-transport properties to achieve their full chargestorage capability.…”
mentioning
confidence: 99%
“…Particularly, as shown in Figure 1 B, when the sheet size of bridging GO decreased from 14.04 to 0.35 μm, the interlayer distance gradually decreases, verifying that the MXene-GO films became more compact. In fact, during the forming process of MXene films, the MXene sheets are mainly affected by the capillary force and the electrostatic repulsion force as schematically shown in Figure 1 C ( Wu et al., 2021 ). Among them, the capillary force tends to make the stacking of MXene sheets denser, while the electrostatic repulsive force tends to make the stacking of MXene sheets looser.…”
Section: Resultsmentioning
confidence: 99%
“…As MXene nanosheets are negatively charged, the interlayer repulsion makes them to form stable aqueous dispersions. Therefore, through adding suitable crosslinking agents [76][77][78] or weakening the repulsion, [79,80] the assembly into 3D structures can be achieved by breaking the dispersion balance.…”
Section: Chemical Assembly Methodsmentioning
confidence: 99%
“…Recently, Yang et al reported a reassembly strategy for producing a flexible MXene-based electrode with tunable porous structure by disassembling MXene microgels from 3D hydrogel and then reassembling with individual MXene nanosheets. [76] The layered arrangement of individual MXene nanosheets formed a densely packed texture, and the well-dispersed MXene microgels introduced pores for ion transport. By controlling the ratio of MXene microgels and individual nanosheets, the density and porosity of the MXene film could be balanced, leading to considerable volumetric capacitance under ultrahigh rate.…”
Section: Assembly Based On the Interaction Of Terminationsmentioning
confidence: 99%